Diverse Roles of F-BoxProtein3 in Regulation of Various Cellular Functions - Zhang, Zhiyang; Bao, Zhengqi; Gao, Penglian; Yao, Junyi; Wang, Peter; Chai, Damin (Frontiers in Cell and Developmental Biology, 2022)
Accumulated evidence shows that the F-box protein 3 (FBXO3) has multiple biological functions, including regulation of immune pathologies, neuropathic diseases and antiviral response. In this review article, we focus on the role of FBXO3 in inflammatory disorders and human malignancies. We also describe the substrates of FBXO3, which contribute to inflammatory disorders and cancers. We highlight that the high expression of FBXO3 is frequently observed in rheumatoid arthritis, leukemia, pituitary adenoma, and oral squamous cell carcinoma. Moreover, we discuss the regulation of FBXO3 by both carcinogens and cancer preventive agents. Our review provides a comprehensive understanding of the role of FBXO3 in various biological systems and elucidates how FBXO3 regulates substrate ubiquitination and degradation during various physiological and pathological processes. Therefore, FBXO3 can be a novel target in the treatment of human diseases including carcinomas.